Physical and mental health well-being of COVID-19 recovered patients: A phenomenological study - Sawsan Abuhammad; Karem H. Alzoubi; Omar F. Khabour; Shaher Hamaideh; Basheer Khasawneh; Maryam El-zubi (PLoS ONE, 2025)
Aim This study aims to describe the experience of COVID-19 recovered patients’ physical and mental health well-being. Method A qualitative research approach was employed utilizing an unstructured interview protocol to explore the experiences of individuals recovering from COVID-19. Data were collected from 30 participants who had recovered from a moderate to severe form of the disease, all of whom required hospitalization with oxygen support during their illness. To gain an in-depth understanding of their post-recovery experiences, grand tour questions were used to facilitate open-ended discussions, allowing participants to fully articulate their perspectives on the impact of COVID-19 on their health and well-being. Results Thematic analysis of the interviews revealed four primary themes related to the post-recovery experiences of COVID-19 patients. Physical health concerns were widely reported, including persistent respiratory difficulties, joint and muscle pain, changes in activity levels, and the worsening of pre-existing health conditions. In terms of cognitive health, participants described experiencing memory loss, difficulty concentrating, and other cognitive impairments that affected their daily functioning. Psychological health challenges were also prominent, with many participants expressing feelings of anxiety, nervousness, loneliness, and sadness, reflecting the emotional toll of their illness and recovery. Additionally, sleep disturbances emerged as a significant issue, with individuals reporting difficulty falling asleep, fragmented sleep patterns, and persistent fatigue. These findings indicate that COVID-19 recovery extends beyond physical healing, affecting multiple aspects of an individual’s overall well-being. Conclusion This study highlights the extensive and multidimensional impact of COVID-19 recovery, affecting physical, cognitive, and psychological health, as well as sleep patterns. The persistence of symptoms such as respiratory issues, cognitive impairments, emotional distress, and sleep disturbances underscores the need for long-term medical and psychological support for recovered patients. These findings emphasize the importance of comprehensive post-recovery care, including rehabilitation programs, cognitive interventions, and mental health services to support individuals in regaining their overall well-being. Future research should focus on developing targeted interventions to address these long-term effects and improve the quality of life for COVID-19 survivors.